Plight of Dryland Farmers Amidst COVID Pandemic: A Rapid Assessment in Crisis Time - Rapaka, Praveen; G., Bhaskar; Kiran, B. Uday (Journal of Agricultural Extension Management, 2022)
This study aims to explore the problems faced by the farmers of KfW project during the COVID pandemic. The data was collected through cluster resource persons from 5 districts of Andhra Pradseh. A total of 280 respondents were selected randomly from the NICE database representing all five districts viz. Anantapur, Chittoor, Kadapa, Kurnool and Prakasam. The main objective of the study is to explore the difficulties of farmers during COVID and also to identify the information needs. After analyzing using descriptive analysis, the results showed the marketing problems, food insecurity, and strategies that farmers followed to market their produce during the lockdown. The study also shed light on the information needs and the preferred mode of receiving the information by farmers